Impacts of cultural practices on consumers' buying behavior in sales promotional activities in the settings of COVID-19 - Rehman, Fazal ur; Javed, Farwida; Shiekh, Sadia Ejaz; Prokop, Viktor (Emerald Group Publishing Limited, 2024)
Purpose: This study aims to explore the impact of cultural practices on consumers' buying behavior in sales promotional activities toward the fashion clothing brands based on the Theory of Black-Box Model under the conditions of COVID-19 at Pakistan.Design/methodology/approachThe study has collected data through questionnaire-based survey from 600 consumers of fashion clothing brands using convenience sampling technique in Pakistan and analyzed through PLS-SEM to find results.FindingsThe results confirmed that cultural practices and sales promotional activities have positive significant relationship with the consumers' buying behavior during the celebration of events, also under the conditions of COVID-19. The study also found that ethnocentrism and xenocentrism are positively associated with cultural practices while social factors, physical factors, product innovation and marketing innovation with sales promotional activities.Practical implicationsThe outcomes provide interesting insights about consumers' assessment toward the sale's promotional activities and cultural practices of fashion clothing brands during the celebration of events and guide the marketing practitioners to develop the customers edifying and environment-oriented business strategies to boost up the buying behavior in crisis situations.Originality/valueAlthough prior research has widely investigated the cultural practices, sales promotion and consumers' buying behavior in various settings, but to the best of the authors' knowledge, this is the first study in these domains.
Vliv kulturních praktik na nákupní chování spotřebitelů při propagačních prodejních aktivitách v prostředí COVID-19
Keywords: Cultural practices; Sales promotion; Buying behavior; Fashion clothing brands; Black-box model; Kulturní praktiky; Podpora prodeje; Nákupní chování; Módní oděvní značky; Black-box model